65+60+55+50+35+75+56x=189

Simple and best practice solution for 65+60+55+50+35+75+56x=189 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 65+60+55+50+35+75+56x=189 equation:


Simplifying
65 + 60 + 55 + 50 + 35 + 75 + 56x = 189

Combine like terms: 65 + 60 = 125
125 + 55 + 50 + 35 + 75 + 56x = 189

Combine like terms: 125 + 55 = 180
180 + 50 + 35 + 75 + 56x = 189

Combine like terms: 180 + 50 = 230
230 + 35 + 75 + 56x = 189

Combine like terms: 230 + 35 = 265
265 + 75 + 56x = 189

Combine like terms: 265 + 75 = 340
340 + 56x = 189

Solving
340 + 56x = 189

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-340' to each side of the equation.
340 + -340 + 56x = 189 + -340

Combine like terms: 340 + -340 = 0
0 + 56x = 189 + -340
56x = 189 + -340

Combine like terms: 189 + -340 = -151
56x = -151

Divide each side by '56'.
x = -2.696428571

Simplifying
x = -2.696428571

See similar equations:

| p*3*r*2=(p+p)*(r+r+r) | | 57=3000 | | x^2-3xy-2=x-3y | | p*3*r*2=6pr | | (-3x-2)(4x+3)=(x-5)(4x+3) | | -5x-11+7x-13=4 | | 3y-5+y-3=180 | | (x-9)(x+1)+8=0 | | -8x+7x=5 | | -8+7x=5 | | (x-9)(x+1)+8x=0 | | 3(x-5)+6(3-x)=5x-13w | | 8+5=213 | | -15=-n+6n | | 2y=8-9x | | 6x^3+30x^2+7x+35=0 | | 75+2x=180 | | -2x-10+4x+25=-2 | | x=-20+3X | | 2(4f+2g)2=8f+2g | | -5x+8+7x=6 | | 2(4f+2g)2=2f(4+2g) | | 3=3tx-5x | | cos(x)+cos(3x)=2sen(6x)cos(x) | | -4=-2(8x-12) | | 3=3t*-5x | | cos(x)+cos(3x)= | | Y-14=4(x-2) | | b=(3.14)(12)2 | | 5x*5x-15x-50=0 | | s*5-22=98 | | 5w-11=89 |

Equations solver categories